MOTHERLY AND NAME СODES IN LESYA UKRAINKA’S AND OLGA KOBYLYANSKA’S ART BIOGRAPHY - Романов, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the Lesya Ukrainka’s and O. Kobylyanska’s relationship with their mothers in comparative context are analysed. There is main problem of depend from mother (this is psychological and biographical factors). The equally important are all private and public markers: human individuality, women essence and creative consciousness. The rupture from the predominating authority is very important for all of called factors of personality, specifically for the integration of personality. This need is very important for an artist, particularly (how in case Lesya Ukrainka) when mother represents of the factors of direct – encouragement – control – in art area. Then the liberation from family dictatorship is not only sublimation over art space, but also the guarantee of this process. For two writers this process manifested itself in quests and final confirm of the literary name.